IFPRI-Nigeria participates in the stakeholders’ consultation workshop on the national fisheries and aquaculture policy (2024-2028) - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
The International Food Policy Research Institute (IFPRI), Abuja Office participated in a two-day (22-23 Aug. 2023) stakeholders’ consultation workshop on the National Fisheries and Aquaculture Policy (2024 -2028) organized by the Federal Ministry of Agriculture and Food Security (FMAFS) with the support of the CGIAR Initiative on Aquatic Foods led by IFPRI and the WorldFish. Specifically, the objectives of the workshop were to: (1) share data, evidence/research findings, and experiences among participants; (2) inform policy directions for the fisheries and aquaculture sector; (3) get a consensus on the major issues and debate on the policy solutions and required investments ; (4) get a consensus on the vision, objectives, and elements of the policy ; (5) get a consensus on the performance indicators, targets and establish a monitoring and evaluation framework for the policy; and, (6) get inputs from experts and key stakeholders on the situation analysis of Nigeria’s fisheries and aquaculture sector.